The burning - Stine, R. L. (New York : Pocket Books, 1993)
The saga of the feud between the Goode and Fier families begins during the witch hunts in Massachusetts in the late seventeenth century.
"An Archway paperback."
"IL 7+"--T.p. verso.
Accelerated Reader AR
Keywords: Horror tales; Witchcraft -- Fiction